The Impact of Teaching Reading Texts Using Reigiluth Elaboration Model in Linguistic Patterns Acquisition and Learning Retention among Third Basic Grade Students in Jordan - Al-Azeez, Ahmed Ali Al-Abed; Al-Maqosi, Yaseen Ali (Arab Journal for Sciences and Research Publishing, 2022)
The study aims at identifying the impact of teaching reading texts using Reigiluth Elaboration Model in linguistic patterns acquisition and learning retention among third basic grade students in Jordan during the first semester of the academic year 2020/2021. The study uses the quasi-experimental approach, and its sample consisted of (60) students from third basic grade students in Doqara Primary School for Boys, which is affiliated with the Directorate of Education in Kasbah Irbid. The sample was randomly divided into two groups; control group and experimental group. To achieve the aims of the current study, two tools were prepared; the first is a test of linguistic patterns, and the second is a test of learning retention after verifying their validity and reliability. The results of the study showed that there are statistically significant differences in both tests between the two groups in favor of the experimental group who studied the cognitive content according to the Reigiluth Elaboration Model compared to the members of the control group. The study reached several recommendations, most notably the employment of the Reigiluth Elaboration Model in the academic content of the branches of the Arabic language curriculum on a broader level.
Keywords: Reigiluth Elaboration Model; Linguistic Patterns; Retention among; Third Basic Grade